Website Programming Information for Al-Ikhlas Aceh Islamic Boarding School - Bayu Andika Simamora (Journal of Innovation and Computer Science, 2025)
With the advancement of information technology, digitalization has become a critical necessity in the education sector. Websites for schools and Islamic boarding schools play a vital role in improving access to information for students, parents, and the community while enhancing communication and interaction efficiency. This study aims to develop and analyze the benefits of implementing an informational website for Al-Ikhlas Aceh Islamic Boarding School. A descriptive qualitative method involving observation and interviews with school stakeholders was applied. The findings indicate that the developed website offers several benefits, including improved access to academic information, better promotion of the school's profile, enhanced communication, and support for students' digital literacy. Therefore, the website is a strategic tool supporting modern and transparent educational management within the Islamic boarding school system.